3D Inkjet Printing of Electronics Using UV Conversion. Issue 10 (17th August 2017) - Saleh, Ehab; Zhang, Fan; He, Yinfeng; Vaithilingam, Jayasheelan; Fernandez, Javier Ledesma; Wildman, Ricky; Ashcroft, Ian; Hague, Richard; Dickens, Phill; Tuck, Christopher
Abstract: The production of electronic circuits and devices is limited by current manufacturing methods that limit both the form and potentially the performance of these systems. Additive manufacturing (AM) is a technology that has been shown to provide cross‐sectoral manufacturing industries with significant geometrical freedom. A research domain known as multifunctional AM (MFAM) in its infancy looks to couple the positive attributes of AM with application in the electronics sector can have a significant impact on the development of new products; however, there are significant hurdles to overcome. This paper reports on the single step MFAM of 3D electronic circuitry within a polymeric structure using a combination of conductive and nonconductive materials within a single material jetting‐based AM system. The basis of this breakthrough is a study of the optical absorption regions of a silver nanoparticle (AgNP) conductive ink which leads to a novel method to rapidly process and sinter AgNP inks in ambient conditions using simple UV radiation contemporaneously with UV‐curing of deposited polymeric structures. Abstract : Printing silver‐nanoparticle inks alongside polymeric inks is challenging due to the high temperatures required for sintering, which can damage the polymer. Here, a method to sinter silver‐nanoparticle inks using ultra‐violet light which is absorbed by the nanoparticles generating localized heat is introduced. A polymeric ink is printed and solidified using the same UV source producing multi‐material 3D structures in one process.